Social Media and Public Pedagogy as Pandemic Resilience - Muh Ariffudin Islam; Ika Anggun Camelia; Muchammad Bayu Tejo Sampurno (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2023)
The rapid transmission of Covid-19 has made the Indonesian government have various kinds of actions and policies to regulate the pattern of life in society, one of which is a policy to carry out activities online. This policy has resulted in a very large public consumption of gadgets, smartphones, or other electronic communication tools, so that information provided by official news centers, social media, or other information platforms is considered a valid source of information. Under these conditions, there is a correlation between social media and public pedagogy which controls and influences each other. This study aims to examine, describe, and bring up realistic facts related to social media content on public education in responding to this pandemic. The method used in this study is a qualitative method with a virtual ethnography approach. This approach refers to ethnographic research that adapts from online sources that specifically examine existing data in cyberspace, especially on social media. The results of this study indicate that social media is one of the online media that can educate the public by presenting information content, prevention, action, and conservation. Social media acts as an entity capable of driving community activities from elements of education, activities, and resilience. The resilience offered by social media in its campaign as public pedagogy, increasingly claims the influence of social media development on social relations. Social media and resilience provide a sense of calm to individuals during the Covid-19 pandemic.